SLC6A and SLC16A family of transporters: Contribution to transport of creatine and creatine precursors in creatine biosynthesis and distribution - Jomura, Ryuta; Akanuma, Shin-ichi; Tachikawa, Masanori; Hosoya, Ken-ichi (Biochimica et biophysica acta. Biomembranes, 2022)
Creatine (Cr) is needed to maintain high energy levels in cells. Since Cr plays reportedly a critical role in neurodevelopment and the immune system, Cr dynamics should be strictly regulated to control these physiological events. This review focuses on the role of transporters that recognize Cr and/or Cr precursors. Our previous studies revealed physiological roles of SLC6A and SLC16A family transporters in Cr dynamics. Creatine transporter (CRT/SLC6A8) contributes to the influx transport of Cr in Cr distribution. γ-Aminobutyric acid transporter 2 (GAT2/SLC6A13) mediates incorporation of guanidinoacetate (GAA), a Cr precursor, in the process of Cr biosynthesis. Monocarboxylate transporter 12 (MCT12/SLC16A12) functions as an efflux transporter for Cr and GAA, and contributes to the process of Cr biosynthesis. Accordingly, the SLC6A and SLC16A family of transporters play important roles in the process of Cr biosynthesis and distribution via permeation of Cr and Cr precursors across the plasma membrane. •SLC6A and SLC16A family transports creatine (Cr) and its precursors.•MCT12 and GAT2/SLC6A13 contribute to the process of peripheral Cr biosynthesis.•CRT participates in Cr distribution to peripheral and central tissues.•In the CNS, SLC6A family mainly contributes to Cr dynamics.•Transporters at the BCSFB participate in cerebral elimination of guanidino compounds.